Pengaruh Persepsi Kualitas Pengguna Transjakarta Pada Rute Manggarai-Blok M - Tazkia Mutiara Dewanti; Tramaditya Kustiawan; Fahri Akbar Kurniawan; Siti Sahara (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Jakarta the capital has several problems due to population density, one of which is traffic congestion. One of these problems is due to the increase in direct driving and the fact that road users do not follow the traffic rules when using private vehicles. Due to the congestion in Jakarta, the government of Jabodetabek Transport Management Board (BPTJ) Ministry of Transport (Kemenhub) launched a public transport service with the concept of Bus Rapid Transit (BRT). Bus Rapid Transit (BRT) or Transjakarta was created to reduce the vehicles, which can be a problem solver to overcome traffic congestion in Jakarta. The analytical method of this article is investigates the perceptions of Transjakarta users and investigates the needs of transport users. From this study, it can be concluded that Transjakarta is probably able to provide safer, faster and more convenient public transport services.